ANALISIS KEPUASAN PELANGGAN DAN PERANCANGAN STRATEGI PROMOSI DALAM UPAYA MENINGKATKAN VOLUME SERVICE KENDARAAN PADA AUTO2000 TABANAN - Anak Agung Ayu Mirah Kencanawati; Lily Marheni; I Made Sarjana; I Gusti Ngurah Agung Maha Putra Udayana (Forum Manajemen, 2022)
This research was conducted at Auto2000 Tabanan which is one of the official Toyota dealers in Bali. The problem faced today is the volume of vehicle service has decreased by 25%. Customer satisfaction is indicated to be one of the causes of the decline in vehicle service volume. The purpose of this study was to determine the level of customer satisfaction and to plan a company's promotional strategy. Based on these problems, service quality (servqual) and SWOT are the methods used to solve the problem. The servqual method is used to measure customer satisfaction, while SWOT is used to formulate a promotional strategy that will be applied by the company with a quantitative descriptive approach. The results obtained with the servqual method is the gap between reality and expectations of the five dimensions of customer satisfaction. The five dimensions of customer satisfaction are negative, which means the company has not been able to meet customer expectations. Overall the company is only able to meet 86% of its customers' expectations. From the SWOT analysis, there are 13 promotional strategies that can be applied by the company to increase the volume of vehicle service